Comparative study on the social behavior of Sambar deer (Rusa Unicolor) in three selected captive facilities in Peninsular Malaysia - Selvarajah, Kushaal; Mohd Nadzir, Mohd Noor Hisham; Annavi, Geetha (Universiti Putra Malaysia Press, 2022)
Sambar deer was up-listed from Least Concern to Vulnerable by the IUCN Red list in 2015. The local government has initiated Ex-situ conservation efforts to boost sambar deer numbers in captivity and reintroduce them into the wild. The reproductive success of sambar deer and their welfare management practices in captivity are important components for effective captive breeding programs. However, there has been a lack of study on sambar deer in recent years, especially about their behavior in captivity. This study aimed to identify environmental factors that may influence the behavior of the captive sambar. Three captive sites were selected and observed for an average of 40 days at each site (minimum 37 days to maximum 43 days, 6 hours/day). A Generalized Linear Model was used to determine the correlation between social behavior and extrinsic parameters. ‘Captive sites’ showed the strongest correlation in behavioral variability environmental settings, such as the size of the enclosure, could force the deer to spend more time in a herd, which increases the frequency in grooming, which was recorded to be highest in Zoo Negara compared to other captive sites. Time of day also significantly influenced certain behavior skewed towards morning slots. It could be due to an adaptive behavior to the feeding time in the captive sites being often in the morning, which caused the deer to rest towards the afternoon. A suggestion would be to create a more erratic feeding schedule to ensure that the deer adapt to behavior variations. An extensive study needs to be done on sambar deer to pinpoint the specifics and better understand these possible influential factors in their behavior.